Flexible electrospun PET/TiO2 nanofibrous structures: Morphology, thermal and mechanical properties. (26th February 2020) - Gallah, Hajer; Mighri, Frej; Ajji, Abdellah; Bandyopadhyay, Jayita
Abstract: In this study, a solvothermal method was used to synthesize anatase titanium dioxide (TiO2 ) nanoparticles in the presence of oleic acid (OA) and oleylamine (OM) as morphology‐directing agents. Functional nanocomposite fibers of poly(ethylene terephtalate) (PET) containing surfactants‐capped TiO2 nanoparticles were developed by electrospinning technique. The morphology, thermal stability and mechanical properties of PET/TiO2 nanocomposite mats were investigated as a function of TiO2 concentration. Morphology investigation showed interesting results in terms of the level of TiO2 dispersion inside the fibers and the improvement of the quality (smoothness) of the fibers' surface when the synthesized nanorhombic TiO2 nanoparticles were used compared to a commercial P25 TiO2 (AEROXIDE P25). The presence of OA and OM on the surface of the nanorhombic synthesized TiO2 led to a significant improvement of TiO2 dispersion inside the PET matrix. Furthermore, the physical interaction between the PET matrix and TiO2 nanoparticles resulted in an enhanced thermal stability, and an increase of the Young's modulus and tensile strength for TiO2 concentration up to 10 wt%.